Integration of Health Education into Nursing Practice to Improve Patient Safety - S. Darmojo, Hardjito; Mardianti, Lina; Rossa, M. Adila; Suciana, Ewin (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2024)
Patient safety is a primary indicator of healthcare quality and is the responsibility of all healthcare workers, particularly nurses, who provide direct patient care. One strategic effort to improve patient safety is through the integration of health education into nursing practice. This study aims to analyze the relationship between the integration of health education into nursing practice and improved patient safety. The study used a quantitative design with a descriptive correlational approach. The study sample consisted of nurses working in inpatient care units, using a purposive sampling technique. Data collection was conducted using a structured questionnaire that measured the level of integration of health education and patient safety. Data analysis was conducted descriptively and analytically using correlation tests. The results showed that the majority of nurses had integrated health education into nursing practice, with a good level of patient safety. Furthermore, their patient safety level was also high. The correlation analysis revealed a positive and significant correlation between the integration of health education and patient safety, indicating that the better the implementation of health education by nurses, the higher the level of patient safety. The discussion of the research findings reveals that structured, ongoing health education supported by effective therapeutic communication can improve patient knowledge, awareness, and participation in maintaining safety during the care process. The conclusion of this study confirms that integrating health education into nursing practice is a crucial strategy for improving patient safety. Therefore, healthcare facilities are expected to strengthen policies, ongoing training, and a culture of patient safety to support the optimization of nurses' educational role